2014
DOI: 10.1371/journal.pone.0113449
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-1/133a Clusters Regulate Adrenergic Control of Cardiac Repolarization

Abstract: The electrical properties of the heart are primarily determined by the activity of ion channels and the activity of these molecules is permanently modulated and adjusted to the physiological needs by adrenergic signaling. miRNAs are known to control the expression of many proteins and to fulfill distinct functions in the mammalian heart, though the in vivo effects of miRNAs on the electrical activity of the heart are poorly characterized. The miRNAs miR-1 and miR-133a are the most abundant miRNAs of the heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
1
24
0
2
Order By: Relevance
“…But, in reviewing their roles and mechanisms in cardiovascular pathophysiology, we observed that both miR-1 and miR-133 change in the same ways during arrhythmia, myocardial infarction, diabetic cardiomyopathy, myocardial hypertrophy, and cardiomyocyte dif-ferentiation. Therefore, it has subsequently been further confirmed that miR-1 and miR-133 do not exist independently, but act as two associated co-transcriptional and cooperative regulatory factors (Besser et al, 2014;Wystub et al, 2013). Furthermore, we also found that miR-1 and miR-133 participate in pathophysiological cardiac processes and play cardioprotective roles through a variety of means.…”
Section: Summary and Prospectssupporting
confidence: 65%
“…But, in reviewing their roles and mechanisms in cardiovascular pathophysiology, we observed that both miR-1 and miR-133 change in the same ways during arrhythmia, myocardial infarction, diabetic cardiomyopathy, myocardial hypertrophy, and cardiomyocyte dif-ferentiation. Therefore, it has subsequently been further confirmed that miR-1 and miR-133 do not exist independently, but act as two associated co-transcriptional and cooperative regulatory factors (Besser et al, 2014;Wystub et al, 2013). Furthermore, we also found that miR-1 and miR-133 participate in pathophysiological cardiac processes and play cardioprotective roles through a variety of means.…”
Section: Summary and Prospectssupporting
confidence: 65%
“…Disturbances in the β‐adrenergic signalling pathway can lead to a longQT phenotype in single miR‐1/133 cluster knockout mice. Moreover, prolonged action potentials were found in cardiomyocytes with a deletion of miR‐1/133a, suggesting that this miRNA cluster is essential for normal electrophysiology in the heart . Matkovich et al demonstrated that miR‐133 had protective effects in miR‐133 transgenic mice undergoing TAC.…”
Section: Therapeutic Microrna‐based Strategies In Heart Failurementioning
confidence: 99%
“…Moreover, prolonged action potentials were found in cardiomyocytes with a deletion of miR-1/133a, suggesting that this miRNA cluster is essential for normal electrophysiology in the heart. 85 Matkovich et al 86 demonstrated that miR-133 had protective effects in miR-133 transgenic mice undergoing TAC. They observed stable levels of miR-133, a significant decrease in myocardial fibrosis, improvement in diastolic function, and no development of hypertrophy.…”
Section: Hypertrophymentioning
confidence: 99%
“…Previous studies have demonstrated that clustered miRNAs may mediate cooperative functions by targeting the same or multiple genes simultaneously (15,16,47). Using bioinformatics analyses, the potential common or similar molecular functions of miR-144-3p, miR-144-5p and miR-451a, which are aberrantly expressed in tumor tissues, were explored in the current study.…”
Section: Initial Eigenvalue Extracted Eigenvalue --------------------mentioning
confidence: 99%
“…An increasing number of studies have demonstrated that miRNA clusters serve important roles in certain biological processes and during oncogenesis (10)(11)(12)(13). A few well-studied miRNA clusters include the miR-17/92, miR-221/222 and miR-1/133a clusters (14)(15)(16). Additional studies have demonstrated that miRNA clusters function more efficiently compared with individual miRNAs alone.…”
Section: Introductionmentioning
confidence: 99%